PERBEDAAN PERSEPSI, MOTIVASI, DAN MINAT MAHASISWA AKUNTANSI ANGKATAN 2008 UNIVERSITAS BRAWIJAYA ATAS PEMILIHAN BIDANG KERJA SETELAH MENJADI SARJANA AKUNTANSI - Chirdiansyah, SE, Yoesdhita Agisio (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research was conducted to find out if there is a difference in perception, motivation and interest of the profession accountant against the selection of profession in the field of accounting and the accounting profession in the field of accounting in non student at Brawijaya University in Malang. This study was also to find out what areas of work will be chosen by the student accounting University of Brawijaya after becoming a Bachelor's degree in accounting. Data collection was done through the dissemination of a questionnaire to students majoring in accounting the 2008. The sample used as many as 60 respondents. The analysis used is discriminant analysis and different test (Mann Whitney Test and T-Test). Different test analysis results showed no difference in perception, motivation and student interest in accounting on accountant against the selection of the desired work field after being a Bachelor's degree in accounting. While based on discriminant analysis, it can be noted that the field of accounting is a field of work desired by student 1 Degree majoring in accounting, University of Brawijaya after being a Bachelor's degree in accounting. Key words: perception, motivation, interest, work field